Plastid Phylogenomics of Dendroseris (Cichorieae; Asteraceae): Insights Into Structural Organization and Molecular Evolution of an Endemic Lineage From the Juan Fernández Islands - Cho, Myong-Suk; Kim, Seon-Hee; Yang, JiYoung; Crawford, Daniel J.; Stuessy, Tod F.; López-Sepúlveda, Patricio; Kim, Seung-Chul (Frontiers in Plant Science, 2020)
Dendroseris D. Don comprises eleven species endemic to the Juan Fernández islands in Chile. They demonstrate spectacular and unusual growth forms of rosette trees with extremely variable morphology and occupy wide ecological ranges on the islands. These unique plants are now highly threatened with extinction with very small population sizes, typically consisting of 10 or fewer individuals in wild. Despite morphological and ecological divergence among species of Dendroseris, their monophyly has been supported in previous studies, but with little resolution among subgeneric groups. We assembled seven complete plastome sequences from seven species of Dendroseris, including representatives from three subgenera, and carried out comparative phylogenomic analyses. The plastomes are highly conserved in gene content and order, with size ranging from 152,199 to 152,619 bp and containing 130 genes, (87 coding genes, 6 rRNA genes, and 37 tRNA genes). Plastid phylogenomic analyses based on both the complete plastome sequences and 81 concatenated coding genes only show Dendroseris nested within Sonchus sensu lato, and also that inter-subgeneric relationships are fully resolved. Subg. Phoenicoseris is resolved as sister to the remaining species of the genus and a sister relationship between the two subgenera Dendroseris and Rea. Ten mutation hotspots from LSC and SSC regions and variable SSRs are identified as potential chloroplast markers for future phylogenetic and phylogeographic studies of Sonchus and related groups.